Changes in actigraphy metrics associated with PROMIS measures after orthopaedic surgery. Issue 6 (18th August 2022) - Giordano, Nicholas A.; Kane, Alexandra; Rodriguez, Ramiro; Papay, Diane; Canales, Bryanna; Kirk, Keri F.; Buckenmaier, Chester C.; Highland, Krista B.
Abstract: Aim: This study examined the feasibility of integrating actigraphy devices into orthopaedic surgical settings to assess the concurrent validity between objective actigraphy data and PROMIS measures. Additionally, the association between changes in actigraphy data and longitudinal changes in PROMIS measures was examined. Methods: Data were collected from 17 participants using actigraphy devices the week prior to and after orthopaedic surgery from 02/2019 to 03/2020. Participants completed PROMIS measures (Physical Function, Sleep Disturbance, Pain Interference) preoperatively and up to 6 months postoperatively. Nonparametric correlations ( r s ) assessed for concurrent validity. Linear mixed‐effects models examined the association between changes in actigraphy data and PROMIS measures. Results: Prolonged wake after sleep onset was associated with increased sleep disturbances ( r s = 0.49; p = 0.045) and pain interference ( r s = 0.51; p = 0.04). Changes in pain interference were correlated with increased awakenings ( r s = 0.54; p = 0.03). Increased wake after sleep onset was associated with worsening sleep disturbance (β = 0.12; p = 0.01) and pain interference scores over the postoperative period (β = 0.12; p = 0.02). Conclusions: This study is among the first to examine changes in objective actigraphy data and longitudinal PROMIS measures following orthopaedic surgery and illustrates the feasibility of incorporating actigraphy into surgical settings to evaluate postoperative recovery. Summary statement: What is already known about this topic? Actigraphy activity and sleep monitoring, paired with robust patient‐reported outcomes, may provide a means by which providers can better understand the patient experience and barriers to recovery after surgery. Often postoperative recovery is only assessed using patient‐reported outcomes (e.g. PROMIS measures), despite consensus groups recommending pairing assessments with objective assessments to better estimate risks for poor postoperative outcomes. Previous studies integrating actigraphy and PROMIS measures together have predominately been limited to paediatric populations or over shorter postoperative periods. What this paper adds? Participants were found to return to preoperative levels of sleep, evident by concurrent changes in both actigraphy and patient outcomes, by 1 week postoperatively. PROMIS Sleep Disturbance and Pain Interference demonstrated concurrent validity with sleep data collected from wrist worn actigraphy devices prior to and after surgery. Prolonged wake after sleep onset was associated with increased PROMIS Sleep Disturbance and Pain Interference scores, while increasing awakenings during sleep were linked to increased PROMIS Pain Interference scores. The implications of this paper: This longitudinal study not only builds upon earlier cross‐sectional investigations with comparable sample sizes that examined the validity of PROMIS measures with actigraphy sleep related data but also uniquely examines how changes in the immediate postoperative period are associated with longitudinal postoperative outcomes. Pairing patient‐reported outcomes with objective actigraphy measures can help improve data collection for nurse scientists and improve nurses' postoperative assessments to help in estimating patient's risks for poor postoperative recovery.